Evaluating the role of angiogenesis in disease behaviour and therapy response in ulcerative colitis - McDonagh, Padraic (Trinity College Dublin. School of Medicine. Discipline of Clinical Microbiology, 2023)
Introduction Ulcerative colitis (UC) is a chronic inflammatory condition with a significant impact on quality of life. In this thesis two small molecule anti-angiogenic and anti-inflammatory agents were used to treat tissue cultured media (TCM) from UC colonic explants. Targeting angiogenesis may provide a novel therapeutic pathway in the management of UC. Methods Patients with a diagnosis of UC attending for a colonoscopy were offered the opportunity to participate. The clinical characteristics of a UC patient cohort were evaluated. Two novel small molecule drugs were used to treat active UC colonic explants. The colonic microenvironment was investigated for angiogenic and inflammatory analyte expression. Both drugs were evaluated for their ability to suppress the release of key inflammatory and angiogenic analytes. Results Both small molecule drugs led to a significant reduction in VEGF-A. VEGF-A is the most potent driver of angiogenesis and has been shown to be associated with increased disease activity in IBD. Both agents also had a significant anti-inflammatory effect, suppressing the secretion of TNF-α, interleukin (IL)-2, IL-8, IL-12p70 and IL-13. Conclusion This study provides evidence that both small molecule agents may have a role in the management of UC. Both molecules display strong anti-inflammatory and anti-angiogenic effects in the UC colonic microenvironment.
Keywords: Ulcerative colitis; angiogenesis; inflammatory bowel disease; dendritic cells; TNF-α; VEGF